Integration of Advanced Biodegradable Polymer Coatings with Solar-Powered Textile Waste Treatment for Reducing Microplastic Pollution in Urban Runoff Systems - Rizqi Elmuna Hidayah; Yohandika Tri Apriliyanto; Beta Arya Ash Shidik (Green Engineering: International Journal of Engineering and Applied Science, 2025)
Microplastic pollution, particularly from textile waste, has become a significant environmental concern, especially in urban runoff systems. These pollutants pose a considerable threat to water quality, aquatic life, and human health. Traditional wastewater treatment methods often fall short in addressing the complexities of microplastic contamination. This research explores the integration of advanced biodegradable polymer coatings with solar-powered textile waste treatment to reduce microplastic pollution in urban runoff systems. Biodegradable polymers, such as polylactic acid (PLA) and polyhydroxyalkanoates (PHA), are highlighted for their potential to efficiently filter microplastics while providing an eco-friendly alternative to conventional filtration technologies. By combining these materials with a small solar-powered unit, the prototype enables an off-grid, low-energy solution to treat textile wastewater in urban environments. The study includes testing the prototype in simulated urban runoff conditions with varying concentrations of microplastics, evaluating key performance indicators such as microplastic removal efficiency, energy consumption, and operational sustainability. Results demonstrate a significant reduction in microplastic concentration, indicating the effectiveness of biodegradable polymer coatings and solar-powered systems in treating urban runoff. The discussion addresses the feasibility of using local biodegradable materials, performance in real-world urban environments, and operational challenges such as maintenance and scalability. This innovative approach is compared with existing microplastic filtration methods, such as membrane filtration and adsorption, highlighting its advantages in terms of sustainability and cost-effectiveness. The findings suggest that this integrated system could offer a viable, low-cost solution for addressing microplastic pollution in urban drainage systems, with potential for widespread urban implementation.